In the ruins - Elliott, Kate, 1958- (Elliott, Kate, 1958- Crown of stars, 2018)
The lost land of the Aoi has returned at last to the earth from which it was cast forth millennia ago. And as tsunamis, earthquakes, and firestorms reshape the very land and seas, darkness descends everywhere. With the war for empire disrupted, all sides must regroup. And though the battle for survival must be the primary focus of all concerned, there are always those eager to seize power, no matter at what cost. Though King Henry demanded with his last breath that Prince Sanglant accept his crown, many may refuse to honor the dying king<U+2019>s wish. Liath, Sanglant<U+2019>s wife, has been excommunicated and unless he agrees to put her aside, his own aunt, Mother Scholastica, is threatening to interdict Sanglant and all who follow him. And though he and Liath long to search for their missing daughter, Blessing, the demands of statecraft hold them hostage to Sanglant<U+2019>s newly constituted court. Henry<U+2019>s wife, Adelheid, is determined to regain control of their empire. But she has let Antonia proclaim herself the new skopos, the Holy Mother who rules over all of the church. And Antonia has already proved herself an extremely dangerous ally. The Aoi are divided between those who seek only to rebuild and warriors determined to claim revenge against the humans. Stronghand, too, is consolidating his gains for his combined Eika/Alban empire, bent on further conquests, drawn in part by the bond he still shares with Alain. And even as Liath seeks out the forbidden magic that could bring back the light of day, new alliances are forming and old ones being abandoned. Only time will tell who<U+2014>if anyone<U+2014>will emerge triumphant as cultures, religions, and races clash in the ultimate struggle for control of this strange new world<U+2026>.